2007
DOI: 10.5897/ajb2007.000-2416
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the exopolysaccharide produced by a whey utilizing strain of Klebsiella oxytoca

Abstract: Physical, chemical and rheological properties of a polysaccharide produced by an isolate of Klebsiella oxytoca were characterized. Freeze dried samples of the polysaccharide were neutral and were completely soluble in water. Samples did not form gels even in the presence of salt treatments. The major monosaccharide constituents of the polysaccharide were rhamnose (37%, w/w) and glucose (34%, w/w). Residues of cellobiose were detected, suggesting that the polysaccharide had a cellulose backbone. The gum was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Gas chromatography revealed that the monosaccharide composition of the crude EPS consisted of rhamnose (Rha; 29.83%), glucose (Glc; 11.21%), galactose (Gal; 52.45%), and mannose (Man; 6.50%); thus, galactose and rhamnose are the major components. These data are in agreement with those found by Dlamini et al (2007) and Feng, Li, Chen (2009), who used different media cultures for the production of EPS from K. oxytoca.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Gas chromatography revealed that the monosaccharide composition of the crude EPS consisted of rhamnose (Rha; 29.83%), glucose (Glc; 11.21%), galactose (Gal; 52.45%), and mannose (Man; 6.50%); thus, galactose and rhamnose are the major components. These data are in agreement with those found by Dlamini et al (2007) and Feng, Li, Chen (2009), who used different media cultures for the production of EPS from K. oxytoca.…”
Section: Resultssupporting
confidence: 93%
“…Some of the properties that contribute to their broad application and, consequently, the realization of extensive research in this area, includes easy production by bacterial fermentation and manipulation by recombinant DNA technology, the ability to retain water and form films, specific rheological behavior, and the potential to improve the immune response (Barbara et al, 2009;Dlamini et al, 2007;Dlamini et al, 2009;Snapper, 2016;Sun et al, 2016;Donot et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the GC analysis, it was concluded that the major sugars for this exopolysaccharide were glucose, mannose, rhamnose and N-acetylglucosamine. The remainder of the peaks could probably be the fragments of partially hydrolysed exopolysaccharide or by-product of hydrolysis reaction (Dlamini et al 2007). A limited number of micro-organisms have been reported to produce polysaccharides that yield rhamnose upon hydrolysis.…”
Section: Discussionmentioning
confidence: 99%